Towards dry fractionation of soybean meal into protein and dietary fiber concentrates. (April 2023) - Kuspangaliyeva, Botagoz; Konakbayeva, Dinara; Tabtabaei, Solmaz
Abstract: Tribo-electrostatic separation of hexane-defatted soybean flour was studied to produce protein- and fiber-rich fractions. The separation was carried out under laminar and turbulent airflow rates and plate voltages ranging from ±1 to ±6.5 kV. The combination of laminar airflow rate and high plate voltage resulted in the highest yield of protein and fiber particles with modest enrichment levels. Accordingly, the soybean flour was enriched in protein from 55.3 to 58.4% and fiber from 15.4 to 19.6%, accounting for 44.4 and 16.8% protein and fiber separation efficiencies, respectively. The distribution of protein and fiber along the negatively charged electrode showed no significant difference in terms of enrichment level. Still, more protein and fiber particles accumulated at the bottom of the electrode, according to the yield results. At 7 LPM and ±6.5 kV, a direct relationship was found between protein content and the average particle size of the fractions. In contrast, a reverse relationship was found for the fiber content. Highlights: Soybean meal flour was fractionated via dry tribo-electrostatic separation. The impact of voltage and flow rate on protein and fiber enrichment was investigated. Laminar airflow and high voltage resulted in modest protein and fiber enrichments. Protein and particle size of the fractions were directly correlated at laminar flow. The protein and fiber were uniformly enriched along the negative electrode.